2007
DOI: 10.1136/ard.2007.072447
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of anti-TNF in rheumatoid arthritis, a comparison between randomised controlled trials and clinical practice

Abstract: Background: Randomised controlled trials (RCTs) evaluating the efficacy of antagonists to tumour necrosis factor a (TNFa) showed high response percentages in the groups treated with active drugs. Objective: To compare the efficacy of anti-TNF treatments for rheumatoid arthritis (RA) patients in RCTs and in daily clinical practice, with an emphasis on the efficacy for patients eligible and not eligible for RCTs of anti-TNF treatments. Methods: First, randomised placebo-controlled trials written in English for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
108
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 176 publications
(121 citation statements)
references
References 23 publications
9
108
1
3
Order By: Relevance
“…This suggests that using a prediction model with variables commonly used for inclusion/exclusion criteria to adjust results from RCTs to a specific daily practice situation can be feasible. In line with Wolfe et al (13), who concluded that the design in RCTs exaggerated the treatment effect because of the selection of patients, and Hyrich et al (57), we also found that a higher DAS28 and older age increased the probability of response next to the treatment. Kievit et al (13) suggested that selection toward high disease activity and continued use of comedication in RCTs could be the probable explanations for the difference in effects of anti-TNF in clinical practice and in RCTs, in line with the findings of our regression analyses.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This suggests that using a prediction model with variables commonly used for inclusion/exclusion criteria to adjust results from RCTs to a specific daily practice situation can be feasible. In line with Wolfe et al (13), who concluded that the design in RCTs exaggerated the treatment effect because of the selection of patients, and Hyrich et al (57), we also found that a higher DAS28 and older age increased the probability of response next to the treatment. Kievit et al (13) suggested that selection toward high disease activity and continued use of comedication in RCTs could be the probable explanations for the difference in effects of anti-TNF in clinical practice and in RCTs, in line with the findings of our regression analyses.…”
Section: Discussionsupporting
confidence: 92%
“…95% CI ϭ 95% confidence interval; anti-IL-1 ϭ anti-interleukin-1; anti-TNF␣ ϭ anti-tumor necrosis factor ␣; DMARD ϭ disease-modifying antirheumatic drug; HAQ ϭ Health Assessment Questionnaire; DAS28 ϭ Disease Activity Score in 28 joints. † Golimumab (a TNF blocker) showed a different treatment effect from the other TNF blockers (as also found earlier by Kievit et al [13]), which led us to the decision to classify this drug separately.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations